Unveiling Trends: A 3-Year Bibliographic Keyword Analysis of Women in Education Research - Suminar, Iin; Arifiyanti, Fitria; Giovanni Ariantara, Raden (WISE Pendidikan Indonesia, 2024)
Research related to gender perspectives in education has increasingly garnered the attention of researchers and practitioners. The focus on women in educational contexts has become particularly prominent in recent years. This article aims to present a comprehensive bibliography of recent research addressing significant issues affecting women in education. It identifies research trends, key topics, and developments in this field over the past three years, providing a valuable reference source for education researchers, practitioners, and policymakers interested in understanding the role of women in education. Key trends include persistent gender disparities in educational attainment, the challenges and opportunities for women in education, and the impact of policies and interventions designed to support women’s educational and professional advancement. The resulting bibliography highlights the progress made and the ongoing challenges in achieving gender equity in education, offering insights into effective strategies and areas requiring further investigation.